2019
DOI: 10.1159/000499088
|View full text |Cite
|
Sign up to set email alerts
|

Viral Metagenomics of Blood Donors and Blood-Derived Products Using Next-Generation Sequencing

Abstract: Transfusion-transmitted infections remain a permanent threat in medicine. It keeps the burden of the past, marked by serious infections transmitted by transfusion, and is constantly threatened by emerging viruses. The global rise of immunosuppression among patients undergoing frequent transfusions exacerbates this problem. Over the past decade, criteria for donor selection have become increasingly more stringent. Although routine nucleic acid testing (NAT) for virus-specific detection has become more sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Furthermore, the timing of sampling is a key factor for the estimation of the prevalence or incidence of viral infections in transplant recipients, since the risk of viral primary infections and reactivations changes over time after transplantation. Among transplant recipients, particularly HSCT patients, blood transfusions may represent a mode of transmission of some viruses that are not screened for in blood product safety tests, despite inactivation procedures (414). As reviewed here, data are, however, conflicting.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…Furthermore, the timing of sampling is a key factor for the estimation of the prevalence or incidence of viral infections in transplant recipients, since the risk of viral primary infections and reactivations changes over time after transplantation. Among transplant recipients, particularly HSCT patients, blood transfusions may represent a mode of transmission of some viruses that are not screened for in blood product safety tests, despite inactivation procedures (414). As reviewed here, data are, however, conflicting.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…In our previous viral SM studies, we often found pandoravirus sequences in CSF of patients with encephalitis and in NTCs ( Perlejewski et al, 2015 ; Bukowska-Osko et al, 2016 ; Moustafa et al, 2017 ). After closer analysis of these sequences (low-complexity reads with nucleotide tandem repeats), they were determined not to represent true signals, but sequencing artifacts and/or contaminants originating in laboratory reagents ( Hjelmso et al, 2017 ; Waldvogel-Abramowski et al, 2019 ).…”
Section: Contaminants Detected In Viral Studiesmentioning
confidence: 99%
“…While SM is being used to characterize the virome using various workflows, it still faces numerous challenges, including the decision regarding best extraction and sequencing methods, the need for host genomic background depletion, the necessity of access to computational resources and highly specialized bioinformaticists, and providing relevant clinical data fast enough to be of clinical value ( Schlaberg et al, 2017 ; Boers et al, 2019 ). Overall, SM approach has allowed for comprehensive surveys of never-before-seen viral communities ( Moreno-Gallego et al, 2019 ; Waldvogel-Abramowski et al, 2019 ; Perlejewski et al, 2020b ). However, SM also detects external contaminant nucleic acids and cross-contaminations, which can affect the interpretation of microbiome data ( Xu et al, 2013 ; Laurence et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This does not allow for comprehensive detection of pathogens from clinical samples (metagenomics analysis) but expands on conventional diagnostic testing where it fails to detect the etiologic agent. Targeted 16S rRNA NGS kits are recently available for specimen microbiome composition profiling and offer a cost-effective method for bacterial taxonomic classification, similarly viral genera can be targeted by combining VirCapSeq-VERT and unbiased NGS workflows [20, 21].…”
Section: Discussionmentioning
confidence: 99%